2020
DOI: 10.2196/19437
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Real-Time Locating System for Contact Tracing of Health Care Workers During the COVID-19 Pandemic at an Infectious Disease Center in Singapore: Validation Study

Abstract: Background In early 2020, coronavirus disease (COVID-19) emerged and spread by community and nosocomial transmission. Effective contact tracing of potentially exposed health care workers is crucial for the prevention and control of infectious disease outbreaks in the health care setting. Objective This study aimed to evaluate the comparative effectiveness of contact tracing during the COVID-19 pandemic through the real-time locating system (RTLS) and re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 22 publications
1
62
0
Order By: Relevance
“…Concurrently, RTLS tags are enabled with tag-tag radio-frequency identification technology to determine close contacts of <=2 meters between staff and patients. Although the location-based radio-frequency identification system in the NCID has been validated by Ho et al [ 12 ], the performance of tag-based technology has yet to be assessed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, RTLS tags are enabled with tag-tag radio-frequency identification technology to determine close contacts of <=2 meters between staff and patients. Although the location-based radio-frequency identification system in the NCID has been validated by Ho et al [ 12 ], the performance of tag-based technology has yet to be assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Hellmich et al [ 11 ] were able to identify twice as many potential contacts of confirmed pertussis cases in an emergency department with RTLS compared with EMR review. Ho et al [ 12 ] also found that the use of location-based RTLSs to complement EMR review increased the sensitivity of detecting health care workers’ contact with COVID-19 inpatients from 47.2% to 77.8%. However, despite the positive outcomes of using RTLSs for contact tracing [ 11 - 13 ], such technologies have largely been confined to health care institutions due to the high costs of infrastructure setup [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 Within local institutions, use of real time location tracking devices and institutional temperature recording systems have been utilized as a method of identifying at risk individuals. 5 , 6 Surveillance is one of the key pillars of infection prevention, enabling early detection and institution of downstream practices that allow reduction in pathogen spread and containment of infection. Syndromic surveillance may allow for an even earlier mobilization of response before the causative pathogen is identified and enhance disease containment.…”
Section: Introductionmentioning
confidence: 99%
“…Given the scale of the response required, technological advances can complement traditional contact tracing methods to introduce efficiencies needed to successfully avert ongoing transmission [ 15 ]. Digital contact tracing using real-time locator systems, including downloadable apps, has gained traction as a direct-to-consumer approach to efficiently identify individuals who may have come into close contact with persons diagnosed with COVID-19 [ 16 , 17 ]. These systems require broad community acceptance and usage to provide sufficient population-wide coverage, as mathematical modelling estimates suggest that high population coverage is needed to effectively reduce transmission [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These systems require broad community acceptance and usage to provide sufficient population-wide coverage, as mathematical modelling estimates suggest that high population coverage is needed to effectively reduce transmission [ 18 , 19 ]. These data further suggest that a combination of direct contact tracing with a digital approach has the highest yield in identifying cases that warrant isolation or quarantine to successfully mitigate ongoing transmission [ 16 ]. However, digital privacy remains a concern, and limited voluntary use of contact tracing approaches hampers the utility of these systems [ 20 ].…”
Section: Introductionmentioning
confidence: 99%